Heritage Industry, or Lithuanian Notions of the Manor in the 21st Century - Kulevičius, Salvijus (Lietuvos istorijos studijos, 2022)
For decades, the notion of a manor was basically unequivocal in the Lithuanian society – it was related to Polish influence (which means it is not ours, Lithuanian). This was the result of political and cultural conflicts between the two nations, a struggle for the power of expression of great narratives and historical memory. The manor with its history and heritage was depicted in negative or at least gloomy colors. Such notions dominated in the consciousness of Lithuanians almost during the whole 20th century. In the second half of the 1980s, the first seeds of alternative or novel notions of the manor emerged in Lithuania. In about 2000, the business discourse appropriated manor culture to create their own notion as developers of products and services for consumers. This paper presents the genesis of this notion, its peculiarities, expressions, and interactions with Lithuanian identity and historical memory.One of the conclusions of the research is that around 2010, a fundamental turning point occurred in the concept and notion of Lithuanian manors, as they came to be associated with native Lithuanian culture and identity – associated, yet not unconditionally accepted. The new role of the manor presents an interesting phenomenon. Manor culture is perceived as attractive because of its different, exotic, and unknown culture.
Keywords: cultural memory; notions; manors; cultural heritage; heritage industry